Resistance to Activated Protein C in Nine Thrombophilic Families: Interference in a Protein S Functional Assay - Faioni, E M; Franchi, F; Asti, D; Sacchi, E; Bernardi, F; Mannucci, P M (Thrombosis and Haemostasis, 1993)
Nine thrombophilic patients who had had previous diagnoses of functional protein S deficiency were reinvestigated. The functional protein S assays gave dose-response curves that were not parallel to those of the reference plasma. The same pattern was true for approximately half of the first-degree relatives of the propositi. When protein S was extracted from the plasma of the patients by immunoabsorption, it had a normal ratio of functional activity to immunologic concentration. Restriction fragment length polymorphism analysis, informative in one family, showed no linkage between the protein S gene marker and the abnormal behavior of the protein S functional assay. All the propositi and 23/36 first-degree relatives were resistant to the prolongation of activated partial thromboplastin time induced by activated protein C. Furthermore, there was striking concordance in all patients and relatives between the abnormal pattern of the protein S functional assay and resistance to activated protein C. We conclude that a plasma-based functional protein S assay is sensitive to activated protein C resistance and this may lead to spuriously low results in the assay. In agreement with the results of others, this study indicates that resistance to activated protein C is a frequent hemostatic defect in selected thrombophilic populations.